Examining Customer Satisfaction Mediates E-Service Convenience and Perceived Quality Effects on Repurchase Intentions in Indonesia - Lira Agusinta; Nadia Yuristika Br Purba; Nuraini Novianti (Green Publisher, 2025)
This study uses customer satisfaction as mediation to determine the effect of e-service convenience and perceived quality on repurchase intention at AirAsia Move Indonesia. Although the app has successfully integrated AirAsia Indonesia's services, several issues, such as poor web quality and lengthy refund processes, cause transaction annoyance. This study aims to understand how these characteristics affect users' intention to repurchase. This research used quantitative methods, by distributing questionnaires to 125 users of the AirAsia Move Indonesia application. Data were processed and analyzed with SEM-PLS 4.1.0.6. The findings of this study are that e-service convenience and perceived quality increase customer satisfaction, thus significantly affecting repurchase intention. Furthermore, customer satisfaction mediates the relationship between e-service convenience and repurchase intention quality. This insight can help project managers improve user experience and increase customer loyalty.